2019
DOI: 10.1016/j.jinorgbio.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The PmoB subunit of particulate methane monooxygenase (pMMO) in Methylococcus capsulatus (Bath): The CuI sponge and its function

Abstract: Highlights  Subunit B (PmoB) of particulate methane monooxygenase (pMMO) is expressed in E. coli.  PmoB and its variants/mutants are expressed in the membranes as Cu I proteins.  The PmoB of pMMO contains a Cu I sponge with high reduction potentials for the Cu sites.  The PmoB proteins show evidence of a dinuclear copper site.  The PmoB-enriched E. coli membranes produce H 2 O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 45 publications
0
45
1
Order By: Relevance
“…However, the pMMO itself has proven challenging to fully characterise, and the nature and location of the site of O 2 activation and methane oxidation remains uncertain. To date, a diiron site located on the PmoC subunit (29), and multiple copper sites of different nuclearities located on separate subunits (PmoA, PmoB and PmoC) have all been suggested as potential active sites (27,(30)(31)(32)(33)(34).…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, the pMMO itself has proven challenging to fully characterise, and the nature and location of the site of O 2 activation and methane oxidation remains uncertain. To date, a diiron site located on the PmoC subunit (29), and multiple copper sites of different nuclearities located on separate subunits (PmoA, PmoB and PmoC) have all been suggested as potential active sites (27,(30)(31)(32)(33)(34).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Recently, those findings have been revised to conclude that pMMO is a protein with mononuclear copper ions at the A , B , and C sites only. , In contrast, there are 12–14 coppers found within each protomer of the functional pMMO according to spectroscopic and biochemical analyses from several other laboratories. It appears that the majority of copper cofactors were inadvertently removed during preparation of the pMMO for protein crystallization. Because the copper cofactors constitute the catalytic machinery of the enzyme, these conflicting views, including the recent debates over the nuclearity of the copper center at the B site ,, and the location of the active site(s) ,, have left a conundrum on understanding the mechanism of pMMO.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that all four characteristic peaks changed during the preparation of Mb–Cu when Cu(II) was added to the Mb solution. When the main peak no longer changed, it was considered that the coordination of Mb and copper was saturated [31].…”
Section: Resultsmentioning
confidence: 99%
“…These unrelated distinct functions of Mb vary with changes in its cell location, physical environment, and complex formation with pMMO, suggesting that Mb may belong to a group of proteins known as moonlighting proteins [29,30]. It was reported that the PmoB subunit is a Cu(I) protein with many copper-binding sites [31]. There is a mononuclear copper site and a dicopper site in the N-terminal sub-domain and “E-clusters” associated with the C-terminal sub-domain of the PmoB subunit [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation